KEY DRIVERS OF CUSTOMER - Losper, Wendy Monica (My University, 2011)
Strategic customer relationships and customer life time value are assets contributing to the creation of shareholder value, a central role of marketing. The delivery of superior customer value requires an understanding of the value propositions which drive customer value, where value relates to the willingness of the customer to pay a premium price. The objective of this research was to gain a better understanding of the key determinants driving customer value. The methodology used was qualitative, indepth interviews in the interpretive paradigm. The sample was drawn from the customer base of a customer oriented manufacturing supply company. Sixteen respondents from a range of industries and expertise provided the data presented in this report. The study found that there was a strong expectation and desire among the customers to partner more closely with the supplier, where the partnering is financially mutually beneficial to both parties. The quality of the supplier’s personnel, in terms of their technical expertise as well as face value, is of key importance in the establishment of the quality relationships expressed to be of value to the customers. The intangible components of the product mix, such as resources, knowledge and skills were identified to be of more value than the physical product. Price and innovation were key customer value drivers not perceived by the supplier to be of importance, thus providing an opportunity for the creation of more customer value. The study found that there was good alignment between the value drivers expressed by the customers to be of value, and the value drivers perceived by the supplier to be of importance. The study may be of value for other companies driven by a customer oriented strategy.
MBA - WBS
Keywords: Customer relations